2002
DOI: 10.1111/j.1550-7408.2002.tb00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Density and Diversity of Protozoa in Some Arid Australian Soils

Abstract: This is the first extensive study of soil protozoa of arid lands. Twenty-six samples from litters, soils, termitaria, and a cyanobacterial crust, collected from central and south Australian arid lands, were analyzed for numbers and species of gymnamoebae, ciliates, and testacea. Amoebae ranged from 1,000-5,000/g of material, and were two orders of magnitude more abundant than ciliates. Both groups increased in abundance and species richness from bare soils through spinifex to mulga to chenopod vegetations. Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
34
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 18 publications
9
34
1
Order By: Relevance
“…However, SSU rRNA sequences of Amoebozoa dominated over those of Alveolata in all non-peat soils. This is in line with cultivation-based studies, which show that small flagellates, especially cercomonads and glissomonads (Rhizaria) (Finlay et al, 2000;Ekelund et al, 2001;Howe et al, 2009) and amoebae represent the numerically dominant soil protists (Schaefer and Schauermann, 1990;Finlay et al, 2000;Robinson et al, 2002). Similarly, other taxonomically highly divergent heterotrophic protist taxa especially abundant in cultivation-based studies such as bodonid and euglenid euglenozoans (Finlay et al, 2000;Geisen et al, 2014a), chrysophytes (Finlay et al, 2000;Boenigk et al, 2005;Chatzinotas et al, 2013), bicosoecids (Ekelund and Patterson, 1997;Lentendu et al, 2014) and heteroloboseans (Geisen et al, 2014a) were identified, but contributed relatively little to the entire protist community.…”
Section: Census Of Soil Protists S Geisen Et Alsupporting
confidence: 80%
“…However, SSU rRNA sequences of Amoebozoa dominated over those of Alveolata in all non-peat soils. This is in line with cultivation-based studies, which show that small flagellates, especially cercomonads and glissomonads (Rhizaria) (Finlay et al, 2000;Ekelund et al, 2001;Howe et al, 2009) and amoebae represent the numerically dominant soil protists (Schaefer and Schauermann, 1990;Finlay et al, 2000;Robinson et al, 2002). Similarly, other taxonomically highly divergent heterotrophic protist taxa especially abundant in cultivation-based studies such as bodonid and euglenid euglenozoans (Finlay et al, 2000;Geisen et al, 2014a), chrysophytes (Finlay et al, 2000;Boenigk et al, 2005;Chatzinotas et al, 2013), bicosoecids (Ekelund and Patterson, 1997;Lentendu et al, 2014) and heteroloboseans (Geisen et al, 2014a) were identified, but contributed relatively little to the entire protist community.…”
Section: Census Of Soil Protists S Geisen Et Alsupporting
confidence: 80%
“…All 10 isolates obtained had an identical 18S rDNA gene sequence, suggesting a close relationship to A. castellani. The apparent lack of Acanthamoeba in the unpolluted soil, though, is rather surprising, since Acanthamoeba species are considered very common in soils (Page, 1988;Rodrı´guez-Zaragoza and Garcı´a, 1997;Robinson et al, 2002). It could be explained, however, by the large food requirements of this amoeba (Bryant et al, 1982), which are probably not met in the unpolluted, mineral soil.…”
Section: The Impact Of Polycyclic Aromatic Hydrocarbons On the Communitymentioning
confidence: 87%
“…In waterlimited environments, one of the most widely accepted theories is the 'fertility' or 'resource island' hypothesis, which states that shrubs create heterogeneity in soils by localizing soil fertility under their canopies (Schlesinger et al, 1996). Indeed, heterotrophic bacteria (Herman et al, 1995) and protozoa (Robinson et al, 2002) have been found to be more abundant under shrubs than in their interspaces. The links between microbial biogeography, local diversity of microorganisms and the factors that shape them represent largely unexplored territory.…”
Section: Introductionmentioning
confidence: 99%